Take the second equation and replace it for where the y is:
2x-(2-x)=4
2x-2+x=4
3x-2=4
3x=6
x=2
y=2-2
y=0
The solution set is (2,0)
Check:
2(2)-0=4
4=4
0=2-2
0=0
I hope this helps!
2007-02-27 03:30:41
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
2x-y=4
-x-y= -2 (transposing the values)
Subtracting the two equations:-
2x - y=4
-2x - 2y= -4
= y=8
Substituting the value of y=8 in equation 1..
2x - 8 = 4
2x = 4+8
2x = 12
x= 12/2
Therefore, x= 2
The solution to the given system is
x=2 , y=6
2007-02-27 03:45:57
·
answer #2
·
answered by suchi- i rock! 1
·
0⤊
0⤋
2x-y=4
y =2-x
you replace y =2-x in 2x-y=4 and get:
2x-(2-x) =4 and now 2x -2+x=4 = 3x-2=4 = 3x=6, so x=2. But you know y =2-x , so y= 2-2 =0.
2007-02-27 03:45:13
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
Add the equations to obtain
2x= 4 + (2 -x) = 6 - x ==> x = 2
Substitution in one of the equations gives y = 0
2007-02-27 03:29:59
·
answer #4
·
answered by physicist 4
·
1⤊
0⤋
2x - y = 4
x + y = 2-------ADD equations
3x = 6
x = 2
2 + y = 2
y = 0
Solution is x = 2, y = 0
2007-02-27 04:16:33
·
answer #5
·
answered by Como 7
·
1⤊
0⤋
x=2
y=0
2007-02-27 03:32:09
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
2x-y=4
2x-(2-x)=4
2x-2+x=4
3x-2=4
3x=4+2
3x=6
x=6/3
x=2
y=2-x
y=2-2
y=0
Your solution is (2,0)
2007-02-27 03:39:33
·
answer #7
·
answered by ema 3
·
1⤊
0⤋
2x-y=4
y=2-x
2x-2x-y=4-2x
y=-2x-4
-y/-1=-2x/-1-4/-1
y=2x+4
y=2-x
2007-02-27 03:41:23
·
answer #8
·
answered by Rudeline C 1
·
1⤊
0⤋